Additional bacterial diseases - Mohan, S.K.; Hagedorn, D.J. (International Center for Tropical Agriculture, 1989)
Bacterial wilt (Corynebacterium flaccumfaciens) has been registered in the USA, but its existence in Latin America is unknown. Drought and temp. more than 32 degrees C are favorable conditions for disease development. The bacterium infects plants through the seed and wounds on aerial plant organs and roots. Control measures suggested include cultural practices and the use of resistant var. Bacterial brown spot (Pseudomonas syringae pv. syringae) produces flecks or necrotic brown lesions on the stem and pods. The bacterium has a wide host range. For efficient disease control, adequate chemical products and the use of resistant var. are recommended. Bean wildfire (P. syringae pv. tabaci) occurs in different bean-growing regions of Brazil and Argentina. Lesions on leaves are small, necrotic, circular to angular, light to dark brown, and surrounded by circular bright halos. No specific control measures are known. The symptoms and damage caused by the disease are illustrated in color. A list of other bacteria pathogenic to beans is also included. (CIAT)